Becoming and unbecoming farm workers in Southern Africa. Issue 4 (2nd October 2017) - Bolt, Maxim
Abstract : More than most forms of employment in Southern Africa, farm work seems to evoke the past. Recent events, however, have foregrounded global integration and cost-cutting casualisation as much as plantation-style racialised hierarchies. Legacies of farmer paternalism, themselves shaped by workers' on-site residence, have inflected changes in agriculture. But these changes invite fresh investigation of what we mean by "farm workers, " as a stereotyped and evocative label intersects with and shapes people's terms of livelihood. This introduction offers an opening framing for five articles that examine how farm workers have become and unbecome, in the past and today. Incorporation into farm hierarchies remains crucial, but the category is political — imposed, claimed, denied, negotiated or transcended in the service of different interests and imaginaries. A wide array of processes shapes becoming a farm worker, from outright coercion to marginalisation, to corporate ethical frameworks. Similarly, unbecoming may be the result of losing a job or non-recognition, or indeed the collapse of a whole sector. The collection's theme has important implications: how workers are defined is crucial amidst falling employment. In these circumstances, "workers" and "workplaces" have significance not only as straightforward descriptors, but as categories with claim-making power and historical resonance.